Extension Program on Knowledge About Balanced Nutrition and Health Examination for Reducing Non-Communicable Diseases in the Baduy Community - Patricia Budihartanti Liman; Yenny Yenny; Alvina Alvina; Laurensius Christian Fernando; Verawati Sudarma; Kartini Kartini (LPPM Universitas Jenderal Achmad Yani, 2026)
Kanekes Village is home to the Baduy indigenous community, which has limited access to educational and healthcare services and continues to strongly uphold its traditional customs and values. Local health center data indicate that hypertension and diabetes mellitus are among the ten most prevalent diseases in the area. Although some community members have adopted relatively healthy dietary habits, their understanding of the Balanced Nutrition Guidelines, which serve as the national reference for healthy eating practices in Indonesia, remains limited. This community service program aimed to improve public knowledge of balanced nutrition while conducting early health screening as a preventive measure against non-communicable diseases (NCDs). The program employed health education sessions, interactive discussions, anthropometric assessments, blood pressure measurements, and examinations of blood glucose, cholesterol, and uric acid levels. Knowledge improvement was evaluated using pre-test and post-test assessments. The activity involved medical students from the Faculty of Medicine, Universitas Trisakti, and a medical student from Universiti Sains Malaysia. The results demonstrated a 25% increase in participants’ knowledge following the educational intervention. In addition, health examinations identified cases of malnutrition and various metabolic disorders among participants. The program effectively enhanced community awareness of balanced nutrition and provided preliminary insights into the health status of the community. Continuous health education and regular health monitoring are recommended to support efforts to reduce morbidity and mortality associated with NCDs, particularly among the residents of Kanekes Village, Banten Province.